Dechlorination and demethylation of ochratoxin A enhance blocking activity of PXR activation, suppress PXR expression and reduce cytotoxicity. (10th October 2020) - Shen, Yuanjun; Shi, Zhanquan; Fan, Jun Ting; Yan, Bingfang
Highlights: The pregnane X receptor (PXR) is activated by structurally diverse PXR agonists. Excessive activation of PXR is implicated in chemoresistance and metabolic diseases. OTA-Cl/M was synthesized and found to block PXR functionality with low cytotoxicity. The blocking activity is achieved by potent downregulation of PXR protein. This novel mechanism points to a broad effect against diverse PXR agonists. Abstract: The pregnane X receptor (PXR) has been established to induce chemoresistance and metabolic diseases. Ochratoxin A (OTA), a mycotoxin, decreases the expression of PXR protein in human primary hepatocytes. OTA is chlorinated and has a methylated lactone ring. Both structures are associated with OTA toxicity. The study was to test the hypothesis that structural modifications differentially impact PXR blocking activity over cytotoxicity. To test this hypothesis, OTA-M and OTA-Cl/M were synthesized. OTA-M lacked the methyl group of the lactone-ring, whereas OTA-Cl/M had neither the methyl group nor the chlorine atom. The blocking activity of PXR activation was determined in a stable cell line, harboring both PXR (coding sequence) and its luciferase element reporter. OTA-Cl/M showed the highest blocking activity, followed by OTA-M and OTA. OTA-Cl/M was 60 times as potent as the common PXR blocker ketoconazole based on calculated IC50 values. OTA-Cl/M decreased by 90 % the expression of PXR protein and was the least cytotoxic among the tested compounds. Molecular docking identified that OTA and its derivatives interacted with different sets of residues in PXR, providing a molecular basis for selectivity. Excessive activation of PXR has been implicated in chemoresistance and metabolic diseases. Downregulation of PXR protein expression likely delivers an effective mechanism against structurally diverse PXR agonists.